(untitled) - SLEZIAK, Mariusz (Trends in education, 2008)
The results of flow visualization and digital image processing methods allowed to obtain detailed conclusions about the hydrodynamics of two-phase flow. Optical techniques of measurement, based on correlation algorithms, allow accurate determination of flow parameters. Quantitative measurements of flow and turbulence characteristics are obtained using DPIV.
Keywords: flow visualization; particle image velocimetry (PIV)